2018
DOI: 10.1002/slct.201801221
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Conformation‐ and Packing‐Controlled Excited State Intramolecular Proton Transfer Induced Solid‐State Fluorescence and Reversible Mechanofluorochromism

Abstract: Excited state intramolecular proton transfer (ESIPT) materials are highly desirable because of their unique solid state fluorescence. Schiff base molecules with appropriate hydrogen donor functional group forms intramolecular H‐bonding, a basis for ESIPT, however, only few molecules show solid state fluorescence. Herein, carbazole based Schiff base molecules 1 (2‐((E)‐(4‐(9H‐carbazol‐9‐yl)phenyl‐mino)methyl)phenol), 2 (2‐((E)‐(4‐(9H‐carbazol‐9‐yl)phenylimino) methyl)‐5‐methoxyphenol), 3 (2‐((E)‐(4‐(9H‐carbazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…[1][2][3][4][5] Unlike the solution properties, supramolecular interactions, molecular conformation and packing exert a significant influence on the fluorescence properties in the solid state. [6][7][8][9] Extensive structure-property studies revealed that a donor (D)-acceptor (A) molecular structure with a twisted nonplanar conformation is an ideal platform for generating solid state fluorescence materials. [10][11][12][13][14] The non-planar conformation hinders aromatic π-stacking and weak intermolecular interactions restrict free intramolecular rotation and facilitate radiative processes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Unlike the solution properties, supramolecular interactions, molecular conformation and packing exert a significant influence on the fluorescence properties in the solid state. [6][7][8][9] Extensive structure-property studies revealed that a donor (D)-acceptor (A) molecular structure with a twisted nonplanar conformation is an ideal platform for generating solid state fluorescence materials. [10][11][12][13][14] The non-planar conformation hinders aromatic π-stacking and weak intermolecular interactions restrict free intramolecular rotation and facilitate radiative processes.…”
Section: Introductionmentioning
confidence: 99%
“…The strong intramolecular H‐bonding in Schiff bases produce aggregation dependent tunable as well as white fluorescence . For Schiff bases, along with intramolecular H‐bonding the molecular conformation also plays important role for making them to solid state fluorescence . The metal chelating functionality of Schiff base ESIPT molecules can also be utilized for fluorescence sensing applications .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The phototautomerisation process between the enol (E*)-keto (K*) is realized through a four-level photo-cycle (E-E*-K*-K-E). In order to achieve multi-colour regulation of solid state emissions for ESIPT molecules, different strategies have been exploited, such as (i) controlling the mode of molecular packing, 13 (ii) aggregation-induced emission (AIE), (iii) restriction of intramolecular rotation (RIR), (iv) torsion/planarity of enol conformers, etc. 5,[14][15][16] Accordingly, requirements become much stricter for the molecular design, organic synthesis of ESIPT molecules and cultivation of a polycrystalline phase.…”
Section: Introductionmentioning
confidence: 99%